Mechanism, prevention and treatment of cognitive impairment caused by high altitude exposure - Chen, Xin; Zhang, Jiexin; Lin, Yuan; Li, Yan; Wang, Han; Wang, Zhanhao; Liu, Huawei; Hu, Yonghe; Liu, Lei (Frontiers in Physiology, 2023)
Hypobaric hypoxia (HH) characteristics induce impaired cognitive function, reduced concentration, and memory. In recent years, an increasing number of people have migrated to high-altitude areas for work and study. Headache, sleep disturbance, and cognitive impairment from HH, severely challenges the physical and mental health and affects their quality of life and work efficiency. This review summarizes the manifestations, mechanisms, and preventive and therapeutic methods of HH environment affecting cognitive function and provides theoretical references for exploring and treating high altitude-induced cognitive impairment.